2015
DOI: 10.1242/jcs.160341
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids inhibit vimentin-dependent cell migration

Abstract: The sphingolipids, sphingosine 1-phosphate (S1P) and sphingosylphosphorylcholine (SPC), can induce or inhibit cellular migration. The intermediate filament protein vimentin is an inducer of migration and a marker for epithelial-mesenchymal transition. Given that keratin intermediate filaments are regulated by SPC, with consequences for cell motility, we wanted to determine whether vimentin is also regulated by sphingolipid signalling and whether it is a determinant for sphingolipid-mediated functions. In cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
(76 reference statements)
1
30
0
Order By: Relevance
“…Ultimately, this effect may be due to the effects of steric hindrance. As the keratin network (and likely the vimentin network, based on recently published studies32 and the data in Fig. 1G) becomes destabilized and reorganizes around the nucleus, the cell volume in the periphery becomes less entangled.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Ultimately, this effect may be due to the effects of steric hindrance. As the keratin network (and likely the vimentin network, based on recently published studies32 and the data in Fig. 1G) becomes destabilized and reorganizes around the nucleus, the cell volume in the periphery becomes less entangled.…”
Section: Discussionmentioning
confidence: 66%
“…SPC also affects the intermediate filament vimentin by phosphorylating S71. This phosphorylation of intermediate filaments leads to an increase in perinuclear keratin and vimentin organization3233. SPC has also been shown to enhance migration through micropores3334 in a manner mirroring the EMT-like effects that have been observed in keratin null or keratin knockdown cells1135.…”
mentioning
confidence: 94%
“…When we used the MDA-MB-435S cells in a recent study on vimentin-dependent migration both SPC and S1P elicited their effects through S1P 2 and the only difference between SPC and S1P responses was a difference in vimentin phosphorylation kinetics. Similarly to the kinetics seen for Lats2 up-regulation in MDA-MB-435S, the effect of SPC on vimentin phosphorylation was sustained while the S1P response was transient in both MDA-MB-435S and C643 cells [29]. Apparently, SPC is able to cause a more prolonged activation of S1P 2 signaling than S1P and this might explain their differing effects on proliferation and Hippo signaling as well.…”
Section: Discussionmentioning
confidence: 52%
“…We found that knockdown of S1P 2 with siRNA (by approximately 70%) strongly attenuated the Lats2 up-regulation (Fig 2A) and inhibition of S1P 2 with JTE013 abolished the effect completely ( Fig 2B). The small G protein Rho and its downstream effector Rho-associated kinase (ROCK) often mediate S1P 2 -induced functions [9] and they are involved in the anti-migratory effect of SPC in MDA-MB-435S [29]. However, when we pre-treated MDA-MB-435S cells with either the Rho inhibitor C3 exotoxin (Fig 2C) or ROCK inhibitor Y27632 (Fig 2D) we saw no attenuation of SPC-induced Lats2 expression.…”
Section: Spc Upregulates Lats2 Via S1p2 and Possibly Akt Inhibition Bmentioning
confidence: 90%
See 1 more Smart Citation